2014
DOI: 10.1189/jlb.6a0214-097r
|View full text |Cite
|
Sign up to set email alerts
|

A pathogenic role for ER stress-induced autophagy and ER chaperone GRP78/BiP in T lymphocyte systemic lupus erythematosus

Abstract: Abnormal regulation of ER stress and apoptosis has been implicated in autoimmune disorders. Particularly, ER stress-induced autophagy and the role of GRP78, or BiP in T lymphocyte survival and death in SLE are poorly understood. This study investigated the pathogenic roles of ER stress-induced autophagy and GRP78/BiP in apoptosis of T lymphocytes. We compared spontaneous and induced autophagy and apoptosis of T lymphocytes in healthy donors and patients with SLE. The molecular mechanism of altered autophagy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…14,34,44 Several reports have implicated a central role for ER stress in the induction of autophagy in the pathogenesis of various neurodegenerative diseases mediated by diverse stressors. [45][46][47][48][49][50] In the current study, we demonstrate for the first time a molecular link between ER stress-mediated activation of autophagy and the induction of astrogliosis that is accompanied with the release of proinflammatory cytokines in cocainetreated human astrocytes.…”
Section: Discussionmentioning
confidence: 89%
“…14,34,44 Several reports have implicated a central role for ER stress in the induction of autophagy in the pathogenesis of various neurodegenerative diseases mediated by diverse stressors. [45][46][47][48][49][50] In the current study, we demonstrate for the first time a molecular link between ER stress-mediated activation of autophagy and the induction of astrogliosis that is accompanied with the release of proinflammatory cytokines in cocainetreated human astrocytes.…”
Section: Discussionmentioning
confidence: 89%
“…In agreement with these studies, we localized splenic proapoptotic markers in RP and WP induced by Pb exposure. Interestingly, a peculiar link between ER stress and abnormal apoptosis was reported in auto-immune disorders and in patients of systemic lupus erythematosus [72]. In light of these data, increase of ER stress and pro-apoptotic cleaved caspase-3 markers in WP, after Pb treatment, could reflect an impairment of immune functions.…”
mentioning
confidence: 93%
“…Houwerzijl et al (5) demonstrated increased vacuoles, plasma membrane thickening and chromatin condensation in the mitochondria and endoplasmic reticulum (ER) of ITP megakaryocytes. This may result in endoplasmic reticulum stress, leading to autophagy (6,7). Autophagy is a biological process, where cytoplasmic macromolecules self-degrade through the lysosomal pathway (8).…”
Section: Introductionmentioning
confidence: 99%